"Twig-like" cerebral vessels are not pathognomonic for ACTA A2 mutations: A case report. Issue 4 (August 2018) - Nagarajan, Krishnan; Swamiappan, Elango; Anbazhagan, Sathiaprabhu; Dalal, Ashwin; Adithan, Subathra; Krings, Timo
ACTA2 mutations are recently described genetically defined abnormalities of blood vessels in various organs of the body with specific abnormalities in cerebral vessels in the form of straightening of all cerebral arteries ("twig-like" pattern), stenosis/occlusions, proximal dilatation, and absent "moyamoya" type of collaterals. We describe a one-and-a half year-old girl child who presented with mild motor developmental delay and on neuroimaging showed septo-preoptic holoprosencephaly, diffuse radial polymicrogyria, and pontine hypoplasia along with magnetic resonance angiographic features suggestive of ACTA2 mutation type of cerebral vessels. However, genetic studies revealed no evidence of ACTA2 mutation, indicating that the "twig-like" pattern may not only be a pathognomonic feature of ACTA2 mutations.